Assessing the effectiveness of the adaptation learning model for dyslexic students' engagement: a quasi-experimental study - Admodisastro, Novia Indriaty; Ismail, Zahian; Mohd Radzuan, Nabilah Filzah; Kamaluddin, Adzhar; Mahmud, Murni; Abdul Hamid, Siti Suhaila (Institute of Advanced Engineering and Science (I A E S), 2024)
Students with dyslexia require individual learning approaches due to different mastery and engagement levels. The conventional approach could not adjust the learning style automatically and burdened the teacher, especially in bigger class sizes. We proposed an adaptive learning model for students with dyslexia (ALMo-DML) that personalised the learning based on the mastery level and behaviour. ALMo-DML can retain the students longer using adaptive elements. This paper examines the effectiveness of the ALMo-DML prototype in increasing student engagement by comparing it with MyLexic, non-adaptive learning using a quasi-experiment. The parameters involve on- task / off-task behaviour, time spent, and usability test. Descriptive statistics, hypothesis testing, Software Usability Scale (SUS), and observation forms were used to measure the engagement parameters. The result shows a longer on-task time with an average of 22 minutes when using the ALMo-DML prototype compared to the non-adaptive application with only 12 minutes (p- value <0.05) using the Mann-Whitney U test. Besides, observation data support the above finding indicating engagement from gestures, keyboard, and mouse clicks. This study proved that ALMo-DML showed a positive effect on the engagement of students with dyslexia compared with non- adaptive learning. Hence, ALMo-DML is highly recommended as a supporting material in helping students with dyslexia.